The diet of spotted cuscus (Spilocuscus maculatus) in natural and captivity habitat - EVI W. SARAGIH; MARIA JUSTINA SADSOEITOEBOEN; FREDDY PATTISELANNO (Nusantara Bioscience, 2010)
Abstract. Saragih EW, Sadsoeitoeboen MJ, Pattiselanno F. 2010. The diet of spotted cuscus (Spilocuscus maculatus) in natural and captivity habitat. Nusantara Bioscience 2: 78-83. The ex-situ conservation of cuscus (Spilocuscus maculatus) under captivating condition is an alternative solution to protect cuscus from extinction. Diets became the main factor in order to support the domestication process. Particular studies on habitat and diet of cuscus have been carried out however there is still limited information on the nutrition aspects of cuscus food. This study aimed to determine the diet type, palatability, and nutrient in both natural habitat and captivating condition. The results indicated that there were 19 and 8 plant species identified as cuscus diets in both natural habitat and captivating condition. Cuscus prefers fruits with astringent and sour taste which is contained high crude fiber and low fat.